2008
DOI: 10.1177/1545968308321773
|View full text |Cite
|
Sign up to set email alerts
|

Potential Predictors of Motor and Functional Outcomes After Distributed Constraint-Induced Therapy for Patients With Stroke

Abstract: The best predictor for motor outcomes after distributed CIT was greater motor ability of the distal part of the upper extremity, which is consistent with the presence of residual motor pathways that may respond to training. The FMA may be of value in stratifying patients for their likelihood to benefit from distributed CIT protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
32
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 56 publications
8
32
2
1
Order By: Relevance
“…Another study limitation includes the lack of information regarding the functional status of each patient subject. Other than FIM score, which has been shown to be an insensitive predictor [33], functional status information is not typically collected during rehabilitation sessions and, thus, reflects a limitation of our rehabilitation system. In addition, this study documented the types and number of reps performed but did not address many other issues that may affect functional improvement, such as "quality" versus "quantity" of movement, duration, types of feedback or cues given, and the cognitive demand of the task.…”
Section: Discussionmentioning
confidence: 99%
“…Another study limitation includes the lack of information regarding the functional status of each patient subject. Other than FIM score, which has been shown to be an insensitive predictor [33], functional status information is not typically collected during rehabilitation sessions and, thus, reflects a limitation of our rehabilitation system. In addition, this study documented the types and number of reps performed but did not address many other issues that may affect functional improvement, such as "quality" versus "quantity" of movement, duration, types of feedback or cues given, and the cognitive demand of the task.…”
Section: Discussionmentioning
confidence: 99%
“…11 Identifying the factors affecting successful outcomes and the patients most likely to respond to the therapy would be informative for clinical guidelines. Although the initial motor status of patients with stroke is viewed as an important factor that influences recovery, 12,13 whether this factor affects the outcomes of RT remains unknown. We therefore investigated the effects of RT on clinical outcomes in patients with chronic stroke by using higher-intensity and lower-intensity RT relative to a duration-matched control treatment (CT) and also examined whether the initial severity of motor deficits and the treatment intensities of RT interact to influence the primary outcome.…”
mentioning
confidence: 99%
“…Constraint-induced therapy (CIT) and its distributed form (dCIT) have been advocated for use in stroke rehabilitation to improve a multitude of functional outcomes (Boake et al, 2007;Dettmers et al, 2005;Lin, Huang, Hsieh, & Wu, 2009;Lin, Wu, Liu, Chen, & Hsu, 2009;Lin et al, 2007;Rowe, Blanton, & Wolf, 2009;Sunderland & Tuke, 2005;Wu, Chen, Chen, Lin, & Yeh, 2012;Wu, Chen, Tsai, Lin, & Chou, 2007). CIT involves constraint of the unaffected upper extremity (UE), allowing the use of only the affected arm daily for 2 wk (Sunderland & Tuke, 2005).…”
mentioning
confidence: 99%
“…CIT involves constraint of the unaffected upper extremity (UE), allowing the use of only the affected arm daily for 2 wk (Sunderland & Tuke, 2005). CIT has been modified to dCIT, a less intensive form that involves 2-3 hr of training of the affected arm combined with 6-9 hr of daily restraint of the unaffected arm for 2-4 wk (Boake et al, 2007;Dettmers et al, 2005;Lin et al, 2007;Lin, Huang, et al, 2009;Wu et al, 2007). Several randomized controlled trials have demonstrated that CIT and dCIT are effective in improving QOL for stroke patients (Lin, Chang, Wu, & Chen, 2009;Lin et al, 2007;Rowe et al, 2009;Wu et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation